Chromatin Dynamics in Lineage Commitment and Cellular Reprogramming - Shchuka, Virlana M. (Genes (Basel), 2015)
Dynamic structural properties of chromatin play an essential role in defining cell identity and function. Transcription factors and chromatin modifiers establish and maintain cell states through alteration of DNA accessibility and histone modifications. This activity is focused at both gene-proximal promoter regions and distally located regulatory elements. In the three-dimensional space of the nucleus, distal elements are localized in close physical proximity to the gene-proximal regulatory sequences through the formation of chromatin loops. These looping features in the genome are highly dynamic as embryonic stem cells differentiate and commit to specific lineages, and throughout reprogramming as differentiated cells reacquire pluripotency. Identifying these functional distal regulatory regions in the genome provides insight into the regulatory processes governing early mammalian development and guidance for improving the protocols that generate induced pluripotent cells.